Diallel analysis for aflatoxin accumulation and fall armyworm leaf-feeding damage in maize. Issue 2 (4th March 2018) - Williams, W. Paul; Windham, Gary L.; Matthews, Gerald A.; Buckley, Paul M.
ABSTRACT: Two major impediments to profitable maize, Zea mays L., production in the southern United States are from feeding by fall armyworm, Spodoptera frugiperda (J.E. Smith), and losses from the production and accumulation of aflatoxin in maize grain. A diallel cross was produced by making all possible crosses among five germplasm lines developed as sources of resistance to fall armyworm leaf feeding and five lines developed as sources of resistance to aflatoxin accumulation. For resistance to both leaf feeding and aflatoxin accumulation, general combining ability (GCA) was a significant source of variation. Specific combining ability (SCA) was significant for fall armyworm feeding only. Estimates of GCA effects for reduced aflatoxin accumulation were significant for Mp715 and Mp719, two lines selected for resistance to aflatoxin accumulation. The GCA effects for reduced fall armyworm damage were significant for all five lines selected for fall armyworm resistance: Mp707, Mp708, Mp713, Mp714, and Mp716.